4(3x+7)-7x=6+5x-2

Simple and best practice solution for 4(3x+7)-7x=6+5x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+7)-7x=6+5x-2 equation:


Simplifying
4(3x + 7) + -7x = 6 + 5x + -2

Reorder the terms:
4(7 + 3x) + -7x = 6 + 5x + -2
(7 * 4 + 3x * 4) + -7x = 6 + 5x + -2
(28 + 12x) + -7x = 6 + 5x + -2

Combine like terms: 12x + -7x = 5x
28 + 5x = 6 + 5x + -2

Reorder the terms:
28 + 5x = 6 + -2 + 5x

Combine like terms: 6 + -2 = 4
28 + 5x = 4 + 5x

Add '-5x' to each side of the equation.
28 + 5x + -5x = 4 + 5x + -5x

Combine like terms: 5x + -5x = 0
28 + 0 = 4 + 5x + -5x
28 = 4 + 5x + -5x

Combine like terms: 5x + -5x = 0
28 = 4 + 0
28 = 4

Solving
28 = 4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 0.75x=3.75 | | y^6-64y^6=0 | | 38-5x=11-8x | | 6-7(A+7)=-3(2-A) | | 3x+12=-18-3x | | -6(3-10m)=102 | | 4(w+2)-8=-20 | | 3+9(9n-9)=651 | | 4(2x+-5)=5x+4 | | y+1=3.6 | | 2z=2.8 | | 171=3(7-5m) | | 2(6x+3)=114 | | 2c-5=c+8 | | 9(2n-7)=-117 | | -8(3n-3)=-192 | | 2y+5=90 | | 35+50=60+45 | | 2x+33=9x-33 | | 3x^3-5x^2-x=0 | | 3.2y-1=90 | | 6k-7(k-3)=-15 | | -104=-8(n+3) | | 7(8+10n)=266 | | 0.04x=2.3 | | 4x-1=90 | | 3(2b-9)=9 | | 5x-30=2x+4 | | x^2+13x=4 | | 4u-6=-18 | | 3(4y-1)=4+5(2y-3) | | 22.3-19.6= |

Equations solver categories